ANTIOXIDANT POTENTIALS AND SIMULTANEOUS ESTIMATION OF QUERCETIN, RUTIN, AND GALLIC ACID IN CURCUMA SPECIES - M, Sowmya Priya; A, Sangilimuthu; M, Karpagavalli; M, Ramkumar; A, Josphin Nirmala (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: This study was designed to provide simple and cost-effective methods to quantify the biologically active phenolic compounds such as rutin, quercetin, and gallic acid from Curcuma species and evaluation of the antioxidant potentials of different parts with different solvent extracts of Curcuma species. Methods: Ultraviolet-visible spectrophotometer was used for the analysis of quercetin, rutin, gallic acid and total flavonoid content of Curcuma species extracts. Antioxidant potentials of Curcuma species extracts were evaluated using 2-2-diphenyl-1-picrylhydrazyl (DPPH) free radical scavenging activity. Results: Ethyl acetate extract of Curcuma aromatica rhizome, aerial part contain higher quantity of quercetin and rutin compared to the other extracts, and also Curcuma species such as Curcuma longa and Curcuma amada contains high antioxidant capacity. The total flavonoid content was high in ethyl acetate extract of Curcuma aromatica as 88.35±0.25 μg/g dry weight of quercetin equivalents. Conclusion: Different extracts of Curcuma species possess good free radical scavenging activity and the IC50 of Curcuma amada aerial part, Curcuma longa aerial part, and Curcuma aromatica rhizome was 61.65±1.75, 62.95±1.85, and 89.40±0.15 (μg/ml), respectively. The Curcuma species contains high total phenolic compounds and antioxidant potentials.